Analisis Penggunaan Limbah Karbit Sebagai Agregat Halus Dan Silicafume Sebagai Subtitusi Semen Terhadap Kuat Tekan Dan Kuat Tarik Belah Beton - Jannah, Miftahul; Sariman, Syahrul; Hijriah, Hijriah (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Waste carbide that is not utilized as well as other pozzolanic materials can be utilized in the contruction sector. Silicfume is part of the mineral admixture in the form of fine pozzolanic material, where the composition of silice is more.. waste carbide which is substituted for sand in the amount of 5% by weight of sand and silicafume which is substituted for cement in the amount of 10%, 20%, and 30% of the weight of cement. The test object used a concrete cylinder with a diameter of 15 cm and a height of 30 cm. The tests carried out were the compressive strength and split tensile strength of the concrete at the age of 28 days. From the results of testing the compressive strength and split tensile strength in normal concrete have 25.89 Mpa and 2.34 Mpa, then the variation of 5% carbide waste is only 26.04 Mpa and 2.87 Mpa, the variation of silicafume 10% is only 26.62 Mpa and 3.05 Mpa, and variations of silicafume 10%, 20% and 30% containing 5% carbide waste had a compressive strength of 26.72 Mpa, 23.78 Mpa, and 19.72 Mpa, as well as the split tensile strength of the concrete. respectively 3.05 Mpa, 2.97 Mpa, and 2.77 Mpa respectively. The relationship between compressive strength and split tensile strength of silicafume concrete and waste carbide is obtained from the equation R2 = 1 where Y = 0,99971x0,34 MPa